Max Einstein: The Genius Experiment - Patterson, James 1947-; Grabenstein, Chris; Johnson, Beverly (New York : JIMMY Patterson Books/Little, Brown and Company, 2018)
Max Einstein and a group of international geniuses use their creativity and curiosity to help solve some of the world's toughest problems with science.
Keywords: Science -- Juvenile fiction -- Experiments; Problem solving in children -- Juvenile fiction; Creative ability -- Juvenile fiction; Genius -- Juvenile fiction; Science -- Fiction -- Experiments; Problem solving -- Fiction; Creative ability -- Fiction; Genius -- Fiction